PENGARUH PERMAINAN PUZZLE TERHADAP KEMAMPUAN DAYA INGAT ANAK KELOMPOK B - AISYAH AISYAH (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2021)
Puzzle is a game that is played with the aim of arranging images, images are randomized beforehand. So people who play it try to arrange it in the frame by connecting pieces or pieces of small images so that they become whole images. Puzzle games given to young children are expected to benefit the children's memory abilities. Pejajaran Kindergarten which in this case the learning model is still classical and the teacher center is still very minimal in providing constructive educational games for early childhood. This is a problem for early childhood, by providing puzzle games, it is hoped that children can improve their memory. According to Jamil (2008:81) This puzzle game tests the speed and accuracy of a child's reaction to a hint given to him. This study uses a pre-experimental research design with the type of One-Group Pre-Test Post-Test. The subjects in this study were group B TK Pejajaran with a total of 25 children. With observation and documentation data collection techniques. While the analysis using SPSS V.20. The results of research with the t test Sig (0,000) < 0,005 means there is an influence between the puzzle game with the child's memory ability. Puzzle games in addition to memory skills can also train children to solve problems, develop eye and hand coordination, develop cognitive and fine motor skills. Keywords : Benefits of Puzzles, children's memory